Septic arthritis in children: diagnosis and treatment - Pääkkönen Markus (DOVE MEDICAL PRESS LTD, 2025)
Acute septic arthritis in children is usually hematogenous. It is more common in boys, and it most often affects the large joints of the lower limb. Diagnosis is based on cultures obtained from the infected joint and is supported by C-reactive protein blood test or ultrasound imaging. Staphylococcus aureus is the most common causative agent and is the primary target for empiric treatment. First-generation cephalosporins and clindamycin are suitable antibiotics. Vancomycin is utilized in areas with high rates of clindamycin-and methicillin-resistant S. aureus. After a short intravenous administration of 2-4 days, a total course of 2 weeks is sufficient in uncomplicated cases. Early antibiotic treatment has significantly improved the prognosis in high-income settings, but uncomplicated recovery is compromised if the treatment is delayed. Complications such as symptomatic osteoarthritis or avascular necrosis of the femoral head develop slowly. A long follow-up of 1-2 years is required to detect all possible sequelae.